2005
DOI: 10.1097/01.icl.0000165280.94927.0d
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of the Number of Lamellae in the Central Region of the Normal Human Corneal Stroma at the Resolution of the Transmission Electron Microscope

Abstract: When assessed at the resolution of the transmission electron microscope, the number of stromal lamellae in the central region of the human cornea are higher (at approximately 240 per cornea) than most previous estimates reported from light microscopy studies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
49
1
1

Year Published

2006
2006
2019
2019

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 61 publications
(53 citation statements)
references
References 19 publications
2
49
1
1
Order By: Relevance
“…The differences may be dismissed as artifacts of the preparative methods, but further work is clearly needed to define the collagen fibril characteristics at other regions of the corneal stroma and to establish the full nature of the possible differences reported by others [13,19] . Similarly, any possible age-related changes [14,20] need to be investigated further as part of specific detailed and systematic studies for both the lamellae [2] , as well as the actual fibrils in human corneas. Such studies are currently in progress.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The differences may be dismissed as artifacts of the preparative methods, but further work is clearly needed to define the collagen fibril characteristics at other regions of the corneal stroma and to establish the full nature of the possible differences reported by others [13,19] . Similarly, any possible age-related changes [14,20] need to be investigated further as part of specific detailed and systematic studies for both the lamellae [2] , as well as the actual fibrils in human corneas. Such studies are currently in progress.…”
Section: Discussionmentioning
confidence: 99%
“…The mammalian corneal stroma is organized into flat sheets called lamellae [1,2] . As revealed many years ago by transmission electron microscopy (TEM), the lamellae are actually composed of collagen fibrils with a relatively small diameter, stated as being between 20 and 50 nm in the earliest papers [3] .…”
Section: Introductionmentioning
confidence: 99%
“…In the human cornea there are distinct anatomical differences between the outermost and the deeper corneal lamellae. The anterior layers have a lamella density some 50% greater than those in the deep layers (Bergmanson et al 2005); they frequently bifurcate and interweave (Radner et al 1998) and are arranged in equal numbers within all orientations within the plane of the cornea. The posterior layers are more hydrated and are stacked rather like plywood, run from limbus to limbus and occur predominantly vertically and horizontally within the eye (Meek et al 1987;Daxer and Fratzl 1997;Aghamohammadzadeh et al 2004).…”
Section: Corneal Lamellaementioning
confidence: 99%
“…However, for cuts deeper than 31%, VisionGraft corneas clearly have less ridges (ridge scores ranged 1.92 to 2.25) than fresh corneas (ridge scores ranged 3.30 to 3.83) 8 . It has been suggested that in fresh corneas, the anterior corneal lamellae have more bridging fibers between them that increase shear strength, and these are relatively lacking in the posterior stroma, 20, 21 the less compactly arranged posterior stromal fiber wrinkled by external pressure such as the action of applanation lens might possibly be one of reasons for ridges on fresh cadaver corneas. We speculated the stronger interlamellar cohesion of VisionGraft corneas could decrease the stromal fiber wrinkling induced by applanation and lead to less ridges on the interface compared with those on fresh corneas.…”
Section: Discussionmentioning
confidence: 99%